Kicking the carbon habit : global warming and the case for renewable and nuclear energy - Sweet, William, 1946- (Columbia University Press, 2006)
With glaciers melting, oceans growing more acidic, species dying out, and catastrophic events like Hurricane Katrina ever more probable, strong steps must be taken now to slow global warming. Further warming threatens entire regional economies and the well being of whole populations, and in this century alone, it could create a global cataclysm. Synthesizing information from leading scientists and the most up-to-date research, science journalist William Sweet examines what the United States can do to help prevent climate devastation. Rather than focusing on cutting oil consumptio.